COVID-19 passes and public health law: Considerations for surveillance and social justice. (20th October 2021) - Lingri, D; Petelos, E; Zeegers, D; Valaris, S; Favaretti, C
Abstract: The first panellist will focus on the jurists view on the legislative proposal on DCC, discuss proportionality of measure, incl. key considerations for DCC and PLF data combinations. A basic overview on the differences between vaccination, certificates, immunity passports and other passes, and the key characteristics of the DCC will be provided. Feasibility in terms of implementing acts across EU Member-States will be elaborated upon, incl. both potential expiry and revocation, as well as potential remedies in case of emerging issues, i.e., right to DCC, but no vaccine, strong contraindication against vaccination, known issues of reduced immunity despite vaccination, etc. Critical aspects with relevance for both the European and the global dimensions, i.e., GDPR and data transfer agreements, secondary use of health data, human-rights' issues, implications for vulnerable groups, etc., will also be discussed.